Utilização da cinza residual do bagaço de cana-de-açúcar na produção de materiais cimentícios alcalinamente ativados - Fernandes Filho , Primo (2012)
The alcalinamente activated cementitious materials have occupied a significant place in world scientific literature, mainly due to its qualities as the mechanical behavior and durability. However, these studies have used preferably activators based on silicates and hydroxides of sodium or potassium and traditional precursors, are aluminosilicates, such as metakaolin and the ceramic waste, as well as the blast-furnace slag. This study evaluated the potential of residual sugar cane bagasse ash, a major waste of Brazil's agribusiness, in the production of cementitious materials alcalinamente activated. The analysis of material characterization and mechanical behavior of the produced material, it was made using the techniques: X-ray fluorescence, X-ray diffraction, infrared spectroscopy, thermal analysis (TG and DTA), Scanning Electron Microscopy scanning optical microscopy and Axial Compressive Strength. It was observed that the predominant compound in the residual sugar cane bagasse ash is silica, with an average content of 80%. After mechanical processing of ash, the methodology adopted to study the solubility of silica in an alkaline environment could extract up to 67,9% of silica present. This silicate was used as activator for the synthesis. Alcalinamente activated composites were produced with the incorporation of various ash contents. Using 100% of residual sugar cane bagasse ash as the precursor material and produced sodium silicate as an activator was possible to obtain a paste with 20 MPa of axial compressive strength. This result is encouraging and this study may contribute to an environmentally sustainable solution to the destination of this waste, rather than being a problem, as it is today.